Respuesta :

Step-by-step explanation:

In the equation 2, make x subject of the formula

[tex]2y - x = 12[/tex]

[tex] - x = 12 - 2y[/tex]

Divide both sides by -

[tex]x = - 12 + 2y[/tex]

Substitute the value of x into equation 1

[tex] \frac{x}{y} = \frac{4}{5} [/tex]

[tex] \frac{ - 12 + 2y}{y} = \frac{4 }{5} [/tex]

Cross multiply

[tex]5( - 12 + 2y) = 4 \times y[/tex]

[tex] - 60 + 10y = 4y[/tex]

[tex]10y - 4y = 60[/tex]

[tex]6y = 60[/tex]

[tex]y = 60 \div 6[/tex]

[tex]y = 10[/tex]

substitute y=10 in equation 2

[tex]2y - x = 12[/tex]

[tex]2(10) - x = 12[/tex]

[tex]20 - x = 12[/tex]

[tex] - x = 12 - 20[/tex]

[tex] - x = - 8[/tex]

[tex]x = 8[/tex]

So therefore

x=8 and y=10

ACCESS MORE